2010
DOI: 10.1128/aem.00650-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Engineered Cerium Oxide Nanoparticles on Bacterial Growth and Viability

Abstract: Interest in engineered nanostructures has risen in recent years due to their use in energy conservation strategies and biomedicine. To ensure prudent development and use of nanomaterials, the fate and effects of such engineered structures on the environment should be understood. Interactions of nanomaterials with environmental microorganisms are inevitable, but the general consequences of such interactions remain unclear, due to a lack of standard methods for assessing such interactions. Therefore, we have ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
230
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(242 citation statements)
references
References 55 publications
9
230
0
3
Order By: Relevance
“…Soybean plants were grown through the seed production stage in soil amended with nano-CeO 2 (0, 0.1, 0.5, or 1 g·kg −1 ) or nano-ZnO (0, 0.05, 0.1, or 0.5 g·kg −1 ). Similar concentrations of these nanoparticles affect hydroponic plants (24,27) and microorganisms (25,28), but the effects on soilcultivated food crop plants are heretofore unknown. Plant growth was monitored by measuring stem length, leaf count, and leaf cover; the latter estimates total leaf area, can indicate plant health, and is affected by water stress (29) and metal exposure (30).…”
Section: Resultsmentioning
confidence: 99%
“…Soybean plants were grown through the seed production stage in soil amended with nano-CeO 2 (0, 0.1, 0.5, or 1 g·kg −1 ) or nano-ZnO (0, 0.05, 0.1, or 0.5 g·kg −1 ). Similar concentrations of these nanoparticles affect hydroponic plants (24,27) and microorganisms (25,28), but the effects on soilcultivated food crop plants are heretofore unknown. Plant growth was monitored by measuring stem length, leaf count, and leaf cover; the latter estimates total leaf area, can indicate plant health, and is affected by water stress (29) and metal exposure (30).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, conjugation of targeting ligands such as aptamers [8], peptides [9], or DNA [10], also confers nanomaterials with targeting capacity toward microorganisms [11][12][13]. Different types of microscopy (e.g., TEM, AFM, SEM) and molecular biology techniques offer powerful approaches to probe bacteria-nanomaterials interactions [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the antibacterial activity of CeO 2 nanoparticles have shown mixed results as well. While some studies have suggested antibacterial activity for CeO 2 nanoparticles (Shah et al 2012), others have indicated no toxic effect of CeO 2 nanoparticles on bacteria (Negahdary et al 2012;Pelletier et al 2010;Thill et al 2006).…”
Section: Introductionmentioning
confidence: 99%